The Problem Based Learning to Enhance Critical Thinking in High School Colloid Lessons - Annisa Indah Herawaty, Annisa Indah Herawaty; Nasution, Mariam; Azizah Putri Hasibuan, Nur (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2026)
In previous studies, students who had low critical thinking skills were due to teacher-centered learning. The purpose of this study is to determine how the Problem Based Learning model affects students' ability to think critically about colloidal material. This research was conducted at SMA N 3 Padangsidimpuan during the even semester of the 2024/2025 academic year, namely from January 23 to February 23, 2025. This study used a quasi experiment to collect 30 students from the experimental and control classes. In the experimental class there were sixteen male students and fourteen female students, and in the control class there were sixteen male students and sixteen female students. The data collection method used was purposive sampling. Critical thinking ability test in the form of an essay test consisting of ten questions analyzed by t-test as the main tool. The hypothesis test results, generated using the SPSS version 28 program, showed that H0 was rejected and H1 was accepted because the data was significant at 0.000 <0.05. This shows that the Problem Based Learning learning model significantly affects students' critical thinking skills at SMA N 3 Padangsidimpuan. The results showed that students' critical thinking skills at SMA N 3 Padangsidimpuan were influenced by the application of a significant Problem Based Learning model and provided motivation for them to learn